2012
DOI: 10.7314/apjcp.2012.13.12.6093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Ultrasonographic Changes of the Breast after Use of Soy Isoflavones

Abstract: Background: Phytoestrogens may be an alternative therapy in control of menopausal symptoms but their definite effects on breast tissue must be determined. Our study aimed to define the clinical and ultrasonographic changes of the breast after use of soy isoflavones in menopausal women. Materials and Methods: Menopausal women with hot flashes were randomly grouped as cases and controls and cases received soy isoflavones for 12 weeks. Breast examination (BE) and ultrasonography (US) were done at 0, 6 and 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In Japan, a case-control study revealed that consumption of soybeans was inversely associated with the risk of breast cancer in women before menopause but not in those post menopause [67]. In a 12-week study, although soy isoflavone elicited some benign ultrasonographic changes of the breast, all of these changes were subclinical and did not need further intervention or follow-up after the study [68]. Moreover, soy isoflavone did not appear to stimulate proliferation of endometrial cells if given over a short term [26].…”
Section: The Risks Of Cancersmentioning
confidence: 99%
“…In Japan, a case-control study revealed that consumption of soybeans was inversely associated with the risk of breast cancer in women before menopause but not in those post menopause [67]. In a 12-week study, although soy isoflavone elicited some benign ultrasonographic changes of the breast, all of these changes were subclinical and did not need further intervention or follow-up after the study [68]. Moreover, soy isoflavone did not appear to stimulate proliferation of endometrial cells if given over a short term [26].…”
Section: The Risks Of Cancersmentioning
confidence: 99%
“…A case-control study in Japan found that the risk of breast cancer was inversely related to soy consumption in premenopausal women, but found no link in postmenopausal women [46]. Although soy isoflavones induced some benign clinical and non-significant ultrasonographic changes of the breast in one 12-week study, none of these changes warranted intervention or follow-up for at least three months after the study [47]. On the other hand, soy isoflavones did not seem to stimulate endometrial proliferation during short-term treatment [17].…”
Section: Effects Of Isoflavones On Menopausal Syndromes and Othersmentioning
confidence: 99%